Coefficient identification for cubically anisotropic elastic media. Issue 4 (3rd May 2016) - Altunkaynak, Meltem; Sacks, Paul; Yakhno, Valery G.
Abstract : In this paper, we consider a version of the inverse problem for a homogeneous, cubically anisotropic, elastic half space. Such a medium is characterized by four constants, and our goal is to study the properties of the mapping which associates to these constants the normal component, but not the transverse components, of a corresponding point source response. This may be viewed as the first stage in a 'layer stripping' approach to the inverse problem when the four parameters are allowed to be depth dependent.